Too many to fail - How bonus taxation prevents gambling for bailouts - Michael Hilmer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Using a simple symmetric principal-agent model of two banks, this paper studies the effects of both bailouts and bonus taxes on risk taking and managerial compensation. In contrast to existing literature, we assume financial institutions to be systemic only on a collective basis, implying support only if they collectively fail. This too-many-to-fail assumption generates incentives for herding and collective moral hazard. If banks can anticipate bailouts, they can coordinate on equilibrium where they collectively incentivize higher risk-taking. A bonus tax can prevent this market failure, even if it is implemented unilaterally: proper bonus taxation reduces risk-taking of the taxed bank and, consequentially, rules out the equilibrium with high risk-taking of both banks. In preventing market failure due to banks collective moral hazard, bonus taxation reestablishes market discipline.
Keywords: H24; M52; G38; 330